Use of Lexical Bundles by Korean EAP Students at Two Different Academic Levels - Hong, Ji-yoon (Foreign Languages Education, 2018)
Lexical bundles have been widely investigated as an indicator of English for Academic Purposes (EAP) writing development in terms of structure and function by exploring the use by students compared to experts. However, little research has compared the use of lexical bundles by second language (L2) Korean EAP students across different academic levels versus first language (L1) English experts with longitudinal corpora. The current study addresses this gap by comparing lexical bundles used both two L2 student corpora and English L1 corpus consisting of introductions of research articles (RAs) and those of term papers. The findings showed the Korean graduate students are in the developmental process in the use of lexical bundles as their academic level advances. However, noticeable development was not found between the students at two levels in terms of function unlike in terms of structure. The pedagogical implications are discussed regarding structural and functional use of bundles for Korean EAP students. KCI Citation Count: 0